Sea-trial verification of a novel system for monitoring biofouling and testing anti-fouling coatings in highly energetic environments targeted by the marine renewable energy industry. Issue 4 (1st July 2021) - Want, Andrew; Bell, Michael C.; Harris, Robert E.; Hull, Mark Q.; Long, Caitlin R.; Porter, Joanne S.
Abstract: A novel system was developed to deploy settlement panels to monitor biofouling growth in situ and evaluate antifouling coatings at depths representative of operational conditions of full-scale marine renewable energy devices. Biofouling loading, species diversity, and succession were assessed at depths ranging from 25-40 m at four tests sites in Orkney (UK) featuring extreme wave and tidal current exposure to more sheltered conditions. Evaluations were carried out over a period of 8 months with intermediate retrieval of samples after 3 months. Early pioneer fouling communities, comprised of colonial hydroids, were succeeded by tube-forming amphipods across sites while solitary tunicates dominated in greater shelter. The highest biofouling loading was observed on high-density polyethylene (HDPE) panels (6.17 kg m −2 ) compared with coated steel (3.34 kg m −2 ) panels after 8 months. Distinct assemblages were present at exposed vs sheltered sites. Better understanding of fouling and antifouling strategies may provide guidance to more effectively manage biofouling impacts in this sector.